If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -4y)(5x + -3y) = 0 Multiply (6x + -4y) * (5x + -3y) (6x * (5x + -3y) + -4y * (5x + -3y)) = 0 ((5x * 6x + -3y * 6x) + -4y * (5x + -3y)) = 0 Reorder the terms: ((-18xy + 30x2) + -4y * (5x + -3y)) = 0 ((-18xy + 30x2) + -4y * (5x + -3y)) = 0 (-18xy + 30x2 + (5x * -4y + -3y * -4y)) = 0 (-18xy + 30x2 + (-20xy + 12y2)) = 0 Reorder the terms: (-18xy + -20xy + 30x2 + 12y2) = 0 Combine like terms: -18xy + -20xy = -38xy (-38xy + 30x2 + 12y2) = 0 Solving -38xy + 30x2 + 12y2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-19xy + 15x2 + 6y2) = 0 Factor a trinomial. 2((3x + -2y)(5x + -3y)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(3x + -2y)' equal to zero and attempt to solve: Simplifying 3x + -2y = 0 Solving 3x + -2y = 0 Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 3x + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 3x + 0 = 0 + 2y 3x = 0 + 2y Remove the zero: 3x = 2y Divide each side by '3'. x = 0.6666666667y Simplifying x = 0.6666666667ySubproblem 2
Set the factor '(5x + -3y)' equal to zero and attempt to solve: Simplifying 5x + -3y = 0 Solving 5x + -3y = 0 Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 5x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 5x + 0 = 0 + 3y 5x = 0 + 3y Remove the zero: 5x = 3y Divide each side by '5'. x = 0.6y Simplifying x = 0.6ySolution
x = {0.6666666667y, 0.6y}
| 6y=6-12x | | x^2-20x+180=0 | | 2002/26 | | 33x-10y=70 | | 8x-(-10x)= | | 14/56=x/100 | | (8m-3)=24 | | I=0.2n | | 15+u-22=9/2 | | p(1-.105)=5907 | | 2a+6b=30 | | 4x-4/2x-2 | | -2?7=-3+t+24 | | x+.105x=5907 | | 75X-100y=400 | | 3x-8(-3x+5x)=24 | | ((8x/x^3-x^6/x^3))^-4/5 | | 4cos^2x+3secx-3-4cosx=0 | | -3.33333333333b=5 | | -3.33333333333b= | | -3=2x-x+y | | 16n^3+64n^2-4n-16=0 | | 7x+0y=180 | | 4/7x63 | | 3/8y-7=-5/8y | | 2y+(-2y)= | | 18*2/5 | | 5(x+3)=9x-11 | | 32×1/4 | | 7/10(190) | | -4(-5+m)=-8 | | f(8)=-1 |